REDUÇÃO DOS DIÂMETROS DE RAMAIS NOS SISTEMAS PREDIAIS DE ESGOTOS SANITÁRIOS - Baroni, Bruno; Oliveira, Lucia Helena de; Comas, Fernanda V (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Sanitary equipment has been improved to become more efficient due the water availability concerns. One consequence may be the impact on the pipes of building drainage system, while using less water in operation, lead to the formation of smaller waves contributing to a poor self-cleaning of pipes. In this sense, this research investigates, in the laboratory, the flows and depths of the flow in drains of a residential building drainage system, under variation of slope, presence or not of continuous flow and pipe diameters, in order to reduce diameters from 100 mm to 75 mm. It was concluded that the reduction of the diameters of the drains contribute to the increase of the velocity of the wave in this part of the system. It was observed that the slope variation does not influence in general performance of the system and the presence of a permanent flow on drain has a negative impact